American moderns : bohemian New York and the creation of a new century - Stansell, Christine (Princeton University Press, 2010)
"In the early years of the new century, an exuberant band of talented individualists thrown together in a shabby neighborhood - a few square blocks called Greenwich Village - set out to change the world. Committed to free speech, free love, and politically engaged art, they swept away late-Victorian sexual prudery, the cult of domesticity, stodgy bourgeois art, and political conservatism as they clamorously declared the birth of the new." "In this group portrait, Stansell depicts this most colorful generation, the men and women who defined modernity for the America to come."--Jacket